Characteristics of pore structure of intersalt shale oil reservoir by low temperature nitrogen adsorption and high pressure mercury pressure methods in Qianjiang Sag - Hongbin Zeng; Furong Wang; Jing Luo; Tao Tao; Shiqiang Wu (地质科技通报, 2021)
In order to more comprehensively characterize the pore structure characteristics of Qianjiang Formation shale oil reservoir in Qianjiang Sag, several shale samples from Well A and Well B with different distances from the source were systematically selected for analyzing and testing, and the pore structure characteristics of shale were comprehensively analyzed by field emission scanning electron microscope, low temperature nitrogen adsorption and mercury intrusion capillary pressure experiment; Making a further study by comparing the field emission scanning electron microscope images, low-temperature nitrogen adsorption and mercury intrusion capillary pressure experimental data on the occurrence space characteristics of retained hydrocarbons in shale; The pore size distribution of connected pores in shale is discussed through the secondary mercury injection experiments on typical shale samples.This study shows that the pore size of Qianjiang Formation shale oil reservoir in Qianjiang Sag is nanometer micron scale, and 2-180 nm clay mineral interlayer pore and dolomite intergranular pore are the two main pore types in this area; The retained hydrocarbon in Well A shale mainly exists in 2-20 nm clay mineral interlayer pores, the content of retained hydrocarbon is low, and the connected pore size is mainly concentrated in the range of 3-15 nm.The retained hydrocarbon in Well B shale mainly exists in 8-100 nm dolomite intergranular pores, the amount of retained hydrocarbon is large, and the connected pore size is mainly distributed in the range of 10-130 nm.The existence of dolomite and clay minerals is conducive to the development of shale reservoir space, but the biogenic dolomite far away from the source is more conducive to the occurrence and mobility of retained hydrocarbon.The research results can provide theoretical support for the exploration and development of shale oil in Qianjiang Sag.